Answer:
![(2x+1) (x+4) = 2x^2 + 9x +8](https://img.qammunity.org/2021/formulas/mathematics/high-school/1qmg2ipydyv23k08e4rsb8hedcb9kaa88k.png)
And then that's our final solution for this case.
Explanation:
One way to solve this problem is using the following property:
![(a+b) (c+d) = ac + ad + bc+bd](https://img.qammunity.org/2021/formulas/mathematics/high-school/tpkpnqp12o4l81tfib8ylxhncxwylyq4em.png)
On this case we know that if we compare this formula with our expression (2x+1) (x+4) we have this:
a= 2x, b =1 , c= x , d = 4
We can find the individual products like this:
![ac= 2x* x = 2x^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/4m51xciw2azehpbfjgkvx26s8a6m6egchq.png)
![ad= 2x*4 = 8x](https://img.qammunity.org/2021/formulas/mathematics/high-school/5eyza5az8r5uhrosy9j5mk64sptovm3c0s.png)
![bc= 1*x = x](https://img.qammunity.org/2021/formulas/mathematics/high-school/3knxbgd70uzkk2p9h3u3jiahx99ospebvf.png)
![bd = 1*4 = 8](https://img.qammunity.org/2021/formulas/mathematics/high-school/ytns2l0wgjo29e0u5276dzhlt89vze0hxd.png)
Then if we replace the values we got:
![(2x+1) (x+4) = 2x^2 + 8x +x+8](https://img.qammunity.org/2021/formulas/mathematics/high-school/yhmna00y6ogkpwvbzyqzdckhiwuogdc5yi.png)
And we can add the two common factors 8x and x like this:
![(2x+1) (x+4) = 2x^2 + 9x +8](https://img.qammunity.org/2021/formulas/mathematics/high-school/1qmg2ipydyv23k08e4rsb8hedcb9kaa88k.png)
And then that's our final solution for this case.